1974
DOI: 10.1677/joe.0.0610501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vasopressin on Toad Bladder Membrane Proteins: Relationship to Transport of Sodium and Water

Abstract: The results support previous findings that vasopressin produces dephosphorylation of a toad bladder membrane protein of 50000 mol. wt. At vasopressin concentrations of 50 mu./ml phosphorylation of this protein was 60 \m=+-\7% of the control level, and maximal natriferic and hydro-osmotic responses were observed in intact bladders. However, at concentrations of vasopressin of 10 mu./ml when a maximal natriferic response but no significant hydro-osmotic response were observed, there was no significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Thus, the sensitivity of the sodium transport response was comparable to that of urea. Water flow was not determined; however, Ferguson and Twite (1974) have reported that sodium transport responds to vasopressin prior to water flow in the toad bladder.…”
Section: Effect Of Vasopressin On Sodium and Urea Transportmentioning
confidence: 99%
“…Thus, the sensitivity of the sodium transport response was comparable to that of urea. Water flow was not determined; however, Ferguson and Twite (1974) have reported that sodium transport responds to vasopressin prior to water flow in the toad bladder.…”
Section: Effect Of Vasopressin On Sodium and Urea Transportmentioning
confidence: 99%
“…The nature of the specific changes in the luminal membrane which might explain induced changes in permeability, however, remains unknown. On biochemical grounds protein membrane components have been implicated in vasopressin-induced movement of water, sodium, and urea [9,10,13,31,38]. Although correlated structural evidence for these components has not been reported, recent freeze-fracture observations by Chevalier et al [5] and us [18] may be pertinent.…”
mentioning
confidence: 99%
“…used in the present work may be associated with direct permeability effects of the hormone (Snart & Sanyal, 1968). It has been shown to give rise to a maximum stimulation of Na+ transport and an increased 02 consumption (Wright & Snart, 1971 a, b;Ferguson & Twite, 1974). The dose-response characteristic for this physiological effect suggests the presence of an octapeptide hormone receptor with an affinity constant of the order 5 x 108 1./mole (450 i.u.…”
Section: Discussionmentioning
confidence: 82%
“…has previously been associated with direct permeability effects of vasopressin and maximum stimulation of Na+ transport (Snart, 1970) whereas the higher doses of vasopressin (100 mu./ml.) have been associated with maximum stimulation of adenylate cyclase activity (Besley & Snart, 1973) dephosphorylation of membrane proteins and stimulation of water transport (Ferguson & Twite, 1974). METHODS Toad bladder preparation.…”
Section: Introductionmentioning
confidence: 99%